The economics of patient safety Strengthening a value-based approach to reducing patient harm at national level - Slawomirski, Luke (OECD Health Working Papers, 2017)
About one in ten patients are harmed during health care. This paper estimates the health, financial and economic costs of this harm. Results indicate that patient harm exerts a considerable global health burden. The financial cost on health systems is also considerable and if the flow-on economic consequences such as lost productivity and income are included the costs of harm run into trillions of dollars annually. Because many of the incidents that cause harm can be prevented, these failures represent a considerable waste of healthcare resources, and the cost of failure dwarfs the investment required to implement effective prevention. The paper then examines how patient harm can be minimised effectively and efficiently. This is informed by a snapshot survey of a panel of eminent academic and policy experts in patient safety. System- and organisational-level initiatives were seen as vital to provide a foundation for the more local interventions targeting specific types of harm. The overarching requirement was a culture conducive to safety